2018
DOI: 10.1108/ijaim-07-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory IFRS adoption, investor protection and earnings management

Abstract: Purpose The purpose of this paper is to examine the effect of investor protection on earnings management before and after IFRS adoption. Design/methodology/approach A sample of 106 companies listed on Germany, France and Belgium stock markets for the pre-IFRS (2000-2004) and post-IFRS (2006-2011) periods was used. This research is based on a comparative study between the pre- and the post-IFRS periods. Findings The results showed that investor protection better explains earnings management after the transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…The different protection of investors' rights by every country distinguishes management behavior in violating investors' rights, including earnings management (Leuz, Nanda, & Wysocki, 2003). Previous studies revealed that investor protection negatively affected earnings management, meaning that strong investor protection can limit management fraud effectively (Chen, Chou, & Wei, 2019;Kouki, 2018;Lourenço et al, 2018). The previous studies also exposed that the specific characteristics could distinguish the level of earnings management, such as leverage (Burgstahler, Hail, & Leuz, 2006;Leuz et al, 2003;Marcel Martins Ardison, Lopo Martinez, & Caio Galdi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The different protection of investors' rights by every country distinguishes management behavior in violating investors' rights, including earnings management (Leuz, Nanda, & Wysocki, 2003). Previous studies revealed that investor protection negatively affected earnings management, meaning that strong investor protection can limit management fraud effectively (Chen, Chou, & Wei, 2019;Kouki, 2018;Lourenço et al, 2018). The previous studies also exposed that the specific characteristics could distinguish the level of earnings management, such as leverage (Burgstahler, Hail, & Leuz, 2006;Leuz et al, 2003;Marcel Martins Ardison, Lopo Martinez, & Caio Galdi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…First of all, it should be stated that due to the lack of research related to the presentation of the dimensions of protecting the interests of shareholders, this research is placed in the hands of the first researchers who attempt to thematize compliance with the material/citizen rights of shareholders at the level of the capital market. Although in the past Ghabri (2022), Wasiuzzaman et al (2022) and Kouki (2018) studied the subject as can be seen, most of the research conducted in this field is quantitative and less research has been conducted through content screening to determine the dimensions of compliance with the material/citizenship rights of shareholders. Therefore, conducting this research can help to fill the theoretical and practical research gap.…”
Section: Introductionmentioning
confidence: 99%
“…These results expand the findings presented by Kempf and Ruenzi (2006) and El Harbi and Toumia (2020), who demonstrated strong influence of past choices on current decisions (i.e., evidence of status quo bias) in the context of different institutions. Thus, they reinforced influence of behavioral bias in individuals' decision-making, especially at the institutional level, contradicting the argument that individuals make rational decisions in any situation, as suggested by mainstream literature (e.g., Jensen & Meckling, 1976;Healy, 1985;Simon, 1990;Barth, Landsman, & Lang, 2008;Kouki, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…The mainstream literature on accounting choices deals with implications of accounting practicing based on individuals' incentives to manipulate earnings under the assumptions of Agency Theory. According to this perspective, managers are rational individuals that tend to maximize their own interests in every choice, considering a set of available and non-exhaustive range of information (Jensen & Meckling, 1976;Healy, 1985;Simon, 1990;Barth, Landsman, & Lang, 2008;Kouki, 2018). According to Lambert (2001), the arguments used by Agency Theory are attractive because allow researchers to explicitly conflicts of interest, incentive problems and mechanisms of control for managers' opportunistic behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation